A taxonomy of learner-player's emotions in serious games - Abir Hamrouni; Fatima Bendella (Serious Games Society, 2023)
The future of video games lies in Affective Games, as the future of learning lies in Affective Learning that due to the proven role of human emotions in how we think and behave. The main goals behind studying emotions in all areas other than psychology and neuroscience are to maximize beneficial emotions, reduce detrimental ones and to develop adaptive systems. The combination of this concept and recent progress in technology has spurred researchers across various fields to focus on incorporating an emotional aspect into human-computer interaction. In Serious Games context, learner-player can experience two types of emotions, the first is related to the learning elements and the second is referred to video games elements. In both learning and video games contexts, recent studies have introduced affective models to conceptualize the influence of emotions within these spheres. However, a discernible trend emerges in the realm of Serious Games research. Notably, the majority of recent studies within this domain exhibit a notable inclination towards prioritizing aspects such as personalized emotion recognition, adaptive gameplay, real-time feedback mechanisms, emotion regulation training, immersive experiences via mixed reality, longitudinal studies, and collaborative cross-disciplinary initiatives. As a result, the nuanced pursuit of affective modeling for learners-players often experiences relegation, yielding precedence to these innovative trajectories. Within this conceptual framework, this article endeavors to examine the interconnection between the emotional experiences of learner-players and the educational and interactive components inherent in serious games.